2008
DOI: 10.1063/1.2945642
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal coherence in thermal ghost imaging

Abstract: We show theoretically and experimentally that lensless ghost imaging with thermal light is fully interpretable in terms of classical statistical optics. The disappearance of the ghost image when the object and the reference planes are located at different distances from the source is due to the fading out of the intensity-intensity cross correlation between the two planes. Thus the visibility and the resolution of the ghost image are determined by the longitudinal coherence of the speckle beam, and no quantum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
63
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 18 publications
0
63
0
1
Order By: Relevance
“…This is because the number M obj = A obj /A coh of coherent areas falling inside the object, which is defined in Ref. [20], is very high and the visibility decreases with the increase of M obj . Moreover, it should be noted that there is, in fact, a different number of coherent areas M (N ) obj within the object for each different order intensity correlation measurement if we define the coherent area (the resolvable area under the focused condition) as the square of the full-width-half-max δy (N ) of the N th-order intensity correlation function.…”
mentioning
confidence: 99%
“…This is because the number M obj = A obj /A coh of coherent areas falling inside the object, which is defined in Ref. [20], is very high and the visibility decreases with the increase of M obj . Moreover, it should be noted that there is, in fact, a different number of coherent areas M (N ) obj within the object for each different order intensity correlation measurement if we define the coherent area (the resolvable area under the focused condition) as the square of the full-width-half-max δy (N ) of the N th-order intensity correlation function.…”
mentioning
confidence: 99%
“…The difference between these two approaches has been widely discussed by the groups of Shih [2], Boyd [3], Lugiato [4], Zhu [5] and Wang [6]. More recently, theoretical and experimental studies [7][8][9][10][11][12][13][14] on lensless ghost imaging with thermal light have drawn new attention; here "lensless" means that no lens is used for imaging the object. The possibility to perform lensless ghost imaging with thermal light was first predicted by Wang and collaborators [6], who proposed in their paper that the thermal source behaves as a phase-conjugate mirror which reflects an object onto itself.…”
mentioning
confidence: 99%
“…The possibility to perform lensless ghost imaging with thermal light was first predicted by Wang and collaborators [6], who proposed in their paper that the thermal source behaves as a phase-conjugate mirror which reflects an object onto itself. The first experiment with a classical pseudothermal source that successfully demonstrated lensless ghost imaging was performed by Scarcelli et al [8,9], which led to a debate [8][9][10][14][15][16] on the question whether twophoton correlation phenomena must be described quantum mechanically, regardless of whether the light source is classical or quantum. Though there is still no consensus on the subject so far, this does not affect potential applications of ghost imaging with thermal light.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The first demonstration of ghost imaging (GI) [1,2] utilized biphoton pairs which were produced by spontaneous parametric down conversion in a nonlinear crystal, hence the phenomenon was interpreted as the result of quantum entanglement of the photon pairs [3]. Subsequently, further theoretical and experimental work showed that GI is also achievable with pseudo-thermal [4][5][6][7][8][9][10] as well as true thermal light [11,12] and can be explained with a classical statistical model [13,14].…”
Section: Introductionmentioning
confidence: 99%